Die Träume Neapels - Bucchetti, Anna (Netherlands : Bos, Andre, 2005)
Naples has many neighborhoods with small betting shops. The daily customers don’t pick numbers at random: some play the numbers which correspond to the dates of birth or death of relatives, others play the numbers of their dreams. Dreams are translated into numbers with the help of the Italian numbers book Grimas and by the knowledgeable owners of century-old lottery offices. A "reasoned bet" happens, for example, when someone has had a dream about his father stepping into a bucket of water. The lottery vendor takes the book out: father is 81, foot is 53, water is 39 and bucket is 4, so these are the numbers to bet on. When a regular customer's brother gets murdered, people even use this incident to stake their bets. The obsession with numbers sometimes reaches hilarious proportions ("which numbers can be derived from a dream about a cockroach with a limp?"), but behind the gambling, there are often tragic stories. A historian sees parallels with Pythagoras' theory of numbers, which is kept alive in Italian popular culture.
Duration: 01:15:00
Keywords: Documentary films